Doppler Effect and its Medical Applications - Hamdi, Ayat Hamid Khalaf; Shnechel Aalj, Um_Albanen Caeser; Al Kaabi, Mustafa Rahman Jabal; Miran, Karar Ali Badri; Sayah Mahdi, Murtadha Jasim (American Journal of Botany and Bioengineering, 2024)
The Doppler effect is a physical phenomenon observed when the frequency or wavelength of waves changes when the source of the wave, the receiver, or both moves. This effect is used in many applications, such as measuring the speed of vehicles using radar, determining the speed of blood flow in the body, and analyzing the speed of stars and galaxies. The Doppler effect is divided into two types: the Doppler effect for sound waves, which includes (the approach of the source: the frequency increases, and the sound becomes higher, the distance of the source: the frequency decreases, and the sound becomes lower) and the Doppler effect for electromagnetic waves, which includes (the approach of the source: the frequency increases, and the light becomes blue, the distance of the source: the frequency decreases, and the light becomes red). Applications of the Doppler effect is represented in radar: measuring the speed of vehicles, aircraft, ships, rain, wind. Ultrasound: measuring the speed of blood flow, diagnosing heart diseases, monitoring the development of embryos. Astronomy: measuring the speed of stars and galaxies, discovering exoplanets. Medical applications: measuring the speed of blood flow in blood vessels, diagnosing heart diseases, monitoring blood flow in the brain. Industrial applications: Measuring the speed of fluid flow, monitoring machine vibrations, measuring the speed of movement of materials in production lines. There are limitations to the Doppler effect, namely the relative Doppler effect: It depends on the speed of the source and the direction of its movement relative to the receiver. The Doppler effect is inaccurate: In some cases, the Doppler effect may not be accurate, such as when there are obstacles or reflections of waves. In general, the Doppler effect is an important physical phenomenon that has many applications in different fields. In this research, we presented a study that includes the types of Doppler effect, its applications and the limitations of its use, and we focused in particular on medical applications